Promoting shared prosperity in developing countries: the relevance of governance from Islamic perspective / Nor Hazila Ismail ... [et al.] - Ismail, Nor Hazila; Mohd Isa, Maizura; Mohd Rashid, Mohamed Eskandar Shah (UiTM Cawangan Johor, 2018)
The extreme inequality in the distribution of wealth, income and opportunity undermines and distorts the sharing of prosperity, democracy, economic health and vitality, ecological balance, physical health and culture of the nations. In April 2013, the issue of greater inequalities and social exclusion reckoned to be the result of economic growth led the World Bank to set the new goals, to end extreme poverty and promote shared prosperity. Interestingly, the approach of the contemporary solution is largely in consonance with the maqasid or objectives of the Shari'ah. Islam is a universal religion and addresses the entire mankind not the believers alone. It is, therefore, no surprise that people irrespective of faith do often think along Islamic lines. This study analyzed the impact of the governance from Islamic perspective on poverty, by adopting a cross-country approach. Specifically, the study examined the impact of Islamic governance structures on the poorest quintiles of the population by evaluating the relationship between the factors and the changes in the per capita income of the poor of the developing countries. This study applied panel regression to examine the significance of the pillars of the governance from the Islamic perspective towards the shared prosperity of the developing countries. It is hoped that this study will help determine if the Islamic pillars of the Islamic Governance can serve as an effective mechanism for poverty eradication in the respective countries.